Effect of sterilization treatment on polyphenol content, antioxidant activity and stability of free and encapsulated herb (Terminalia arjuna) added milk drink - Sawale, Pravin; Patil, Girdhari Ramdas; Hussain, Shaik Abdul; Singh, Ashish Kumar; Singh, Ram Ran Bijoy (Indian Journal of Dairy Science, 2019)
In the current investigation, effect of heat treatment (121ºC/15 min) on stability, polyphenols content and antioxidant activity of milk drinks added with alcoholic extract Terminalia arjuna were determined. Four different vanilla chocolate flavoured milk drink samples viz. supplemented with free (Drink 1) and encapsulated (Drink 2) form of T. arjuna and their respective controls (Control 1 & Control 2) devoid of herbal extract were prepared. The sterilization treatment reduced the antioxidant activity and phenolic content of drink 1, while reverse trend was noticed for drink 2. Heat coagulation time, measure of stability of milk drinks, revealed that addition of T. arjuna extract led to a decrease in pH (Drink 1 – pH 6.67 to 6.65 and Drink 2 –pH 6.67 to 6.66) of milk drinks thus led to destabilization of casein micelles as evidenced from the appearance of flakes in heat stability tubes. Control samples showed type A kind of HCT-pH profile, while Drink 1 and Drink 2 showed type B kind of HCT-pH profile. The study indicated that encapsulation is effective in preserving the bioactivity of T. arjuna extract during heat treatment.